(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: The indwelling devices are the foreign body that increase the process of bio film formation in the body. The present study was carried out to detect bio film formation by Staphylococci spp. recovered from different indwelling devices received from hospitalized patients at Lahore General Hospital. Methods: The present study was a cross sectional diagnostic study. All specimens obtained from the hospital were processed in the microbiology section of pathology department of Post Graduate Medical Institute. Staphylococci species were identified through routine microbiological and biochemical tests. Antimicrobial susceptibility was determined by modified Kirby-Bauer disc diffusion method. Staphylococcal isolates along with the controls were allowed to form bio film by Tube Method (qualitative) and Microtiter Plate Assay (quantitative). Data analysis was one by using SPSS 19.0. Results: Bio film formation in the patients with more than one indwelling device was greater as compared to the patients with single device. Intravascular catheters were found more noteworthy for bio film formation. The possibility and strength of bio film formation increases with the number of days a medical device remains in the body (p-value<0.05). Conclusion: The microorganisms with multi drug resistance showed very strong bio film formation. In the patients with indwelling devices, bio film formation is more pronounced with intravascular catheter and in the patients with more than one-inserted devices. Moreover, bio film formation is more pronounced if medical indwelling device is allowed to retain for more number of days inside the body.